Laboratory-acquired injuries in medical laboratory: a survey of three referral medical laboratories from year 2001 to 2005 - I Anuar,; F Zahedi,; A Kadir,; A.B Mokhtar, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Background : The occupationally acquired accident and injuries in Malaysian medical laboratories are still largely unexplored prior to this survey. Some of these questions are attempted in this survey and act as source of reference for the number and accident injuries in medical laboratories in the area of Klang Valley and also in Malaysia. Methods : This survey was carried out based on recordable cases throughout the calendar year of 2001 to 2005 from 3 main medical laboratories of Hospital Kuala Lumpur (HKL), Hospital Universiti Kebangsaan Malaysia (HUKM) and Pusat Perubatan Universiti Malaya (PPUM). Results : The average annual incident rate for this three medical laboratories is 2.05/100 full time equivalent (FTE) employees. The annual incident rate in individual medical laboratory is 2.04/100 FTE (HKL), 2.07/100 FTE (HUKM) and 2.04/100 FTE (PPUM) employees, respectively. The most common injury that is 25.3% of the total cases reported was due to cuts by sharp objects and the second most common injury was exposure to biohazard and chemical substances which constitutes 19.9% of the total cases. Needle prick injury (16.8%), fire (8.4%), fall/slip (6.3%) and gases leak and locked in cold room were reported as one case each. Conclusion : The average incident rate from this study is remarkably similar compared with the incident injury rate reported by BLS (2006) which is 2.1/100 FTE in the average size of medical laboratory and diagnostic. Besides this incident rate of injury and illness as a comparison, it also can be used as a benchmark to evaluate the safety performance among medical laboratories in Malaysia.